Consumptive Behavior Reviewed from Self-Esteem and Brand Image in Teenagers - Putri Mahendra, Dinda; Grice Karaeng, Panca; Anggra Oktaviani, Feby (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to determine the relationship between self-esteem and brand image and consumer behavior in adolescents. This research uses a quantitative approach using a questionnaire. The psychological measuring instruments used in this research include the consumer behavior scale, self-esteem scale and brand image scale. The sample in this study was female students in class X SMA YP Unila Bandar Lampung with a total of 215 students. The data analysis technique for this research uses multiple regression analysis assisted by the SPSS 21.0 for Windows program to see the relationship between self-esteem and brand image and consumer behavior in teenagers. The results of this research show that self-esteem and brand image have an effective contribution of 27.5% to related variables and 72.5% are generated by other variables outside this research. The self-esteem variable has no relationship with consumer behavior in adolescents, marked with a significance value of 0.444 (p>0.05), while the brand image variable shows a relationship with consumer behavior, marked with a significance value of 0.001 (p<0.05).